2020
DOI: 10.1155/2020/2046248
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEIS3 Generates Cetuximab Resistance through c-Met and Akt

Abstract: Introduction. Although cetuximab has been widely used in the treatment of colon cancer, a large number of patients eventually develop drug resistance. Therefore, it is essential to clarify the mechanism of drug resistance. Methods. In this study, we combined in silico analysis and a single guide RNA (sgRNA) library to locate cetuximab-sensitive genes. Cell proliferation, apoptosis, and cell cycle were assessed to validate the change in cetuximab sensitivity. Finally, western blotting was performed to detect ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Several studies have demonstrated the participation of the Met signaling pathway in the evolution of different types of cancer[ 28 , 33 - 35 , 83 ]. Moreover, this receptor is overexpressed and/or can be aberrantly activated by several mechanisms in CRC cells, triggering tumor development and progression[ 28 , 36 , 38 , 59 ]. A recent study addresses the relationship between the HGF/Met axis and cytokines such as PTHrP in bone metastasis and renal cell cancer progression[ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the participation of the Met signaling pathway in the evolution of different types of cancer[ 28 , 33 - 35 , 83 ]. Moreover, this receptor is overexpressed and/or can be aberrantly activated by several mechanisms in CRC cells, triggering tumor development and progression[ 28 , 36 , 38 , 59 ]. A recent study addresses the relationship between the HGF/Met axis and cytokines such as PTHrP in bone metastasis and renal cell cancer progression[ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Met overexpression or its dysregulation can lead to malignant cell transformation and contributes to the development and progression of different types of cancer including colorectal tumors[ 28 , 32 - 35 ]. Moreover, Met dysregulation is also associated with drug resistance in colon cancer cells[ 32 , 35 , 36 ]. Several studies demonstrated the overexpression of this RTK in tumor tissue of CRC patients; in this regard, its inhibition is being widely investigated as a complementary treatment to usual therapies[ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that MEIS2 promotes cell migration and invasion in CRC ( 27 ). And MEIS3 can modify the sensitivity to cetuximab via c-Met and Akt ( 28 ). Overexpression of SNAI1 sustains stemness maintenance and promotes invasion in numerous cancers, including CRC ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Тот факт, что ПТГрП и его рецептор PTHR1 были обнаружены в нормальном и толстокишечном эпителии [32], ясно указывает на то, что ПТГрП является фактором, который действует как локальный регулятор посредством паракринного/аутокринного пути [33]. Эти исследования вместе с другими, проведенными in vitro [34], предоставили информацию о том, как [62]. Несколько исследований продемонстрировали сверхэкспрессию этого рецептора в опухолевой ткани пациентов с КРР.…”
Section: роль птгрп в прогрессии клеточного цикла пролиферации и мигр...unclassified